O significado do trabalho entre os jovens na transição de estudante universitário a profissional - Melo, Simone Lopes de (2002)
The present study analyses the variability of the meaning of the work among young people on the transition from university to professional life, divided according to: university levels, knowledge area and graduation course. A hundred seventeen young people answered the questionaries structured on the components of the meaning of work. Semi-structured interviews were also made with parts of the sample about the themes related to the meaning of work on this way the information of the questionaries became complete. The answers of the interviews were studied through the analysis of the thematic contents. The results of such analysis and the answers of the questionaries were registered on the data base SPSS for Windows. The results of the statistic analysis made indicated that: (1) the centrality of work and the articulations among stronger spheres do not present variability according to level, area or course; (2) the course makes more difference values factors and descriptives factors than area and level; (3) the hierarchy of values presents variability according to area and the descriptive hierarchy presents variability according to course; (4) the level makes more difference specific attributes of the meaning of the work than area and course; (5) the standards of the meaning of work do not present variability according to level, area and course, but present variability according to type of the work market evaluation and planning the future work. In summary, the meaning of work present variability according to level, area and course of the young people, when studied in facets, except for the work centrality